2015
DOI: 10.3109/2000656x.2015.1034726
|View full text |Cite
|
Sign up to set email alerts
|

Minimal packing duration in close reduction for nasal bone fracture treatment

Abstract: The present study demonstrated that 1-day packing had comparable postoperative outcome with reducing the patients' discomfort. As such, a longer packing duration was not needed to achieve stable results one day is a reasonable packing time for most nasal bone fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Pain caused by removal of nasal packs after closed reduction of nasal bone fractures is a common problem. There have been reports of reduced pain when these packs are retained for shorter periods, when the sphenopalatine ganglion is blocked, and when preemptive analgesia is used [2][3][4]. Several studies have suggested that injection of a topical anesthetic agent into nasal packs prior to their removal may reduce pain after septoplasty, although the effects are controversial [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Pain caused by removal of nasal packs after closed reduction of nasal bone fractures is a common problem. There have been reports of reduced pain when these packs are retained for shorter periods, when the sphenopalatine ganglion is blocked, and when preemptive analgesia is used [2][3][4]. Several studies have suggested that injection of a topical anesthetic agent into nasal packs prior to their removal may reduce pain after septoplasty, although the effects are controversial [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal packing is usually removed at 3–5 days after the operation. Following the study of Choi et al [6] in 2015, the clinical outcome of nasal bone surgery is not altered by different duration of nasal packing. In this study, the author removed nasal packing on postoperative day 4, which is roughly average values of duration of nasal packing.…”
Section: Discussionmentioning
confidence: 97%
“…. According to Dong et al, one day nasal packing group had good clinical outcome and decreased post operative discomfort when compared with 3 and 4 days packing groups [4]. Closed reduction can be done under local anesthesia 3 days after trauma which showed decreased post operative pain and nasal bleed after manipulation.…”
Section: Discussionmentioning
confidence: 97%